Pendampingan Penataan Lingkungan melalui Konsep Bank Sampah dan Pembuatan Sampah Organik - Lestari, Sri; Nurasiah, Nurasiah; winanti, winanti; Yusuf, Yusuf; Tiara, Beby; Sakhroji, Sakhroji; Basuki, Sucipto; Basuki, Teguh Insan Pembangunan (IAHN Gde Pudja Mataram, 2025)
The low level of public awareness about environmental cleanliness and the sorting of organic and inorganic waste is a problem that continues to occur from day to day. Garbage officers are late in collecting garbage, adding to the problem. The purpose of this activity is to provide understanding and education to the public about organizing a clean environment. The activity lasted one day and the public's enthusiasm was very high. The resource person delivered material about waste banks as one solution. This activity is expected to provide understanding and education to the public to realize the importance of maintaining the environment and living healthily.